Legal Protection Clothing Wholesale Trade With A Contract Of Sale Note - Ridho Syahputra Manurung (International Journal of Educational Research & Social Sciences, 2022)
One of the legal protections can be given to a business activity in order to ensure the protection of a business so that it continues to run well. Therefore, consumer protection is very necessary from the background above. In the case study of paper, the formulation of the problem is as follows, How is the Relationship Between Business Actors and Consumers in Using Sales Notes, What are the Factors Causing the Occurrence of Achievement In Sales, and how to use it to know the Legal Protection for Merchants Who Use Sales Notes Resulting in Default. The type of research carried out is empirical analysis using a case study approach. At the Central Wholesale Market, Medan Market Center with field research, the data collection techniques used are primary data and secondary data consisting of interviews at the Central Wholesale Market, Medan Market Center. The conclusion of this thesis is the relationship between business actors and consumers, namely consumers can obtain sufficient information to fulfill consumer needs. The factors that cause this default are due to two possibilities, namely: the first is the merchant himself because the assessment is done subjectively, the second is the fault of the buyer, either intentional or negligent or beyond his ability. The advice that can be given is that it is hoped that wholesalers can be more careful in making sales, especially clothing wholesalers so that consumers can avoid actions that result in default.